Design and test of a waveguide filter for reflected electromagnetic waves - C. Fransoo; M. Nishiura; S. Kubo (AIP Advances)
A high power gyrotron system is used for plasma production and sustainment by electron cyclotron resonance heating (ECRH) in fusion reactors. An ECRH system in the Large Helical Device uses gyrotrons with megawatt output power. This megawatt electromagnetic wave transmitted through a circular corrugated waveguide is partially reflected back to the gyrotron and can be a cause of unstable gyrotron oscillations. The reflected beam may also propagate at an angle relative to the waveguide axis. To reduce the reflected beam while retaining as much of the forward-propagating gyrotron beam as possible, we aim to optimize the length of a filter consisting of a gap with absorbing walls between waveguide sections in a transmission line. A semi-analytical model is developed using diffraction theory to calculate the transmitted power of the HE11 mode as a function of filter gap distance for a wide range of beam angles, including a perfectly aligned beam to approximate the forward gyrotron beam. Before implementing this filter, we use a vector network analyzer to measure the scattering parameters for an experimental mock-up of this filter with 88.9 mm inner diameter waveguides, gap distances between 0 and 600 mm, and beam angles between 0° and 4°. These sophisticated models are used to inform the gap filter design and length optimization.